2014
DOI: 10.1136/bcr-2013-201124
|View full text |Cite
|
Sign up to set email alerts
|

Sclerosing stromal tumour of the ovary presenting as precocious puberty: a rare neoplasm

Abstract: A 7-year-old Indian girl presented with symptoms of excessive development of breasts, early menarche, growth of pubic hairs, accelerated growth and abdominal distension. On clinical examination, a large right abdominopelvic mass was palpable. MRI revealed a large, heterogeneous, solid and cystic tumour in the right adnexal region, suggestive of an ovarian neoplasm. The hormonal profile showed markedly elevated oestradiol and low follicle-stimulating hormone levels. Clinical diagnosis of precocious puberty with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…However, in 1975, Damjanov et al reported the production of steroid hormones by SSTs [ 28 ]. Androgens and, less frequently, estrogens can lead to menstrual disturbances and signs of virilization or precocious puberty, as reported in several studies [ 8 , 12 , 21 , 25 , 26 , 27 , 29 , 30 , 31 , 32 , 33 , 34 ]. Menstrual irregularities are very common in the first two years after menarche; therefore, this symptom may be underestimated in this population or simply attributed to a physiologically abnormal hormonal production.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…However, in 1975, Damjanov et al reported the production of steroid hormones by SSTs [ 28 ]. Androgens and, less frequently, estrogens can lead to menstrual disturbances and signs of virilization or precocious puberty, as reported in several studies [ 8 , 12 , 21 , 25 , 26 , 27 , 29 , 30 , 31 , 32 , 33 , 34 ]. Menstrual irregularities are very common in the first two years after menarche; therefore, this symptom may be underestimated in this population or simply attributed to a physiologically abnormal hormonal production.…”
Section: Discussionmentioning
confidence: 92%
“…However, the latter is mostly bilateral, lacks the characteristic pseudolobular pattern of sclerosing stromal tumors, and usually occurs during the sixth and seventh decades of life. Furthermore, Krukenberg’s tumor signet ring-like proteins contain mucin rather than lipids, and show nuclear atypia and mitotic activity [ 19 , 34 ]. Sclerosing stromal tumor cells were mainly positive for vimentin, SMA, and inhibin, strongly suggesting their stromal origin.…”
Section: Discussionmentioning
confidence: 99%
“…This entity occurs preferentially in young patients and adolescents, with a mean age at diagnosis of 29 years; postmenopausal cases, however, have been observed [62]. Although patients present with bleeding, menstrual irregularities [63], or pelvic pain [8], SST is typically not associated with hormonal manifestations [61], despite precocious puberty or association with pregnancy having been reported [64,65]. Rare cases have been reported in association with Meigs syndrome [66,67].…”
Section: Sclerosing Stromal Tumormentioning
confidence: 99%
“…The characteristics of the included studies (18 'adult' [11,12,[20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35] and 16 'paediatric' studies [36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51]) are provided in Table 1. The mean age of patients included was 10.8 years in the paediatric and 46.9 years in the adult studies.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%